Hemoglobin Level, Energy Intake, and Body Mass Index of Kebersihan, Keindahan, Kenyamanan Lingkungan Workers in an Academic Institution - Carmelia Cantika Maharani; Reni Farenia; Pandji Irani Fianza (Althea Medical Journal, 2017)
Background: Productivity is a priority that is required from every worker. Work productivity of each person is different. The important factors of work productivity are hemoglobin level, energy intake, and body mass index (BMI). The objective of the study was to identify  hemoglobin level, energy intake, and BMI of  Kebersihan, Keindahan, Kenyamanan Lingkungan (K3L) workers in Universitas Padjadjaran, Jatinangor. Methods: A descriptive study was carried out to 80 K3L workers in  Universitas Padjadjaran on October 2014. The total number of 80 workers was chosen with cluster random method. Primary data consisted of hemoglobin level measured by Hemocue®Hb 201+, dietary consumption recall (2x24 hours), and anthropometry data (weight and height). The collected data were analyzed and presented by frequency tabulation and percentage.Results:The study showed that more than a half of subjects (77%) had normal hemoglobin level. The majority of subjects (47%) had low energy intake. Most of subjects (59%) had normal BMI, 12% subjects were underweight, 18% subjects were overweight, and 11% subjects were obesity. Conclusions: The majority of K3L workers have normal hemoglobin level, energy intake deficiency, and normal BMI. DOI: 10.15850/amj.v4n2.1089